Influência da neurotransmissão espinal sobre o tônus vasomotor simpático no modelo de hipertensão renovascular - Milanez, Maycon Igor De Oliveira [UNIFESP] (2017)
Previous studies showed a higher glutamate and angiotensin II (ANG II) receptors activation in the rostral ventrolateral medulla (RVLM) that may lead to sympathoexcitationin renovascular hypertensive rats (2K-1C). However, the role of the spinal cord neurons on the renal sympathoexcitation remains unclear in this model. Thus, we aimed to assess the influence of spinal glutamatergic (ionotropic receptors) and AT1 angiotensin II (Ang II) receptors on the renal sympathetic nerve activity (rSNA) in renovascular hypertension. Male Wistar (250-300g) rats were distributed into two independent groups: control (CTL) (n=21) and 2K-1Crats (n=19). Renovascular hypertension was induced by clipping the renal artery with a silver clip. After six weeks a catheter (PE-10) was inserted into the subarachnoid space and advanced to the T10-11 vertebrae level in urethane-anaesthetized rats (1,2 g/Kg, iv). The effects of intrathecal (i.t.) injection of kynurenic acid (KYN) or losartan (Los) on mean blood pressure (MAP) and rSNA were analyzed for 2 consecutive hours. KYN i.t. injection induced a larger and significant fall on rSNA in the 2K1C compared to control group (CTL x 2K1C: -8 ± 3 x -52 ± 9* spikes/s after 120´). Los i.t. injection also evoked a larger and significant fall in rSNA in the 2K1C compared to control group from 80’ after losartan i.t. administration (CTL x 2K1C – 80 min: -10 ± 2 x -32 ± 6*; 100 min: -15 ± 4 x -37 ± 9*; 120 min: -12 ± 5 x -37 ± 8* spikes/s). KYN decreased BP similarly in CTL and 2K-1C groups, however, Los significantly decreased MAP in the 2K1C group only. Moreover, we found a reduction in the renal baroreflex gain post i.t. of Kyn in CTL and 2K-1C groups. The i.t. administration of Los evoked an increase in the renal baroreflex gain, but only for sympathoinhibitory reflex responses in the 2K-1C group, and reduced the sympathoexcitatory gain in CTL group. Therefore, our data show that ionotropic spinal cord excitatory aminoacid and AT1 angiotensin II receptors play an important role in the control of rSNA in the 2K-1C model that may contribute to the maintenance of hypertension. Changes in rSNA induced by arterial baroreceptor reflex are in part dependent of AT1 angiotensin II and glutamatergic receptors in the spinal cord in 2K1C and control rats. The origin of those projections remains unclear.